2007
DOI: 10.1007/s10995-007-0224-1
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Maternal Infections and Preeclampsia: A Systematic Review of Epidemiologic Studies

Abstract: In our analysis, any infection (bacterial or viral) was associated with a two-fold higher risk of preeclampsia. This association may provide a potential explanation for preeclampsia-related inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 65 publications
3
84
1
6
Order By: Relevance
“…Thus UTI can take into account to developing severe PE in pregnant women. Similar results were found in studies of Easter and colleagues and Rustveld and colleagues, they also concluded that UTI during pregnancy increases the risk of PE (Easter et al, 2015;Rustveld et al, 2008). Hill and colleagues performed a case control study and found that the frequency of UTI in women with PE were19 percent higher than controls (Hill et al, 1986).…”
Section: Discussionsupporting
confidence: 71%
“…Thus UTI can take into account to developing severe PE in pregnant women. Similar results were found in studies of Easter and colleagues and Rustveld and colleagues, they also concluded that UTI during pregnancy increases the risk of PE (Easter et al, 2015;Rustveld et al, 2008). Hill and colleagues performed a case control study and found that the frequency of UTI in women with PE were19 percent higher than controls (Hill et al, 1986).…”
Section: Discussionsupporting
confidence: 71%
“…Several viruses have been associated with adverse pregnancy outcomes and Adenoassociated-virus-2 is associated with preeclampsia [19]. Bacterial and viral infections increase the risk of preeclampsia two-fold [20]. Our previous work in rodents demonstrating that activation of TLR3 by poly I:C (a viral mimetic) during mid-gestation elicits preeclampsia-like symptoms supports the notion that infection during pregnancy contributes to the cause of preeclampsia [11,21].…”
Section: Role Of Interleukin-4 In Preeclampsiamentioning
confidence: 54%
“…Recently, TLRs were shown to be distributed in human uteroplacental tissues and when bound to their respective ligands, such as pathogen-associated molecular patterns (PAMPs) and endogenous danger-associated molecular patterns (DAMPS), trigger the activation of pro-inflammatory immune cells and production of pro-inflammatory cytokines [17,18]. Previous studies implicate viral infections to be associated with adverse pregnancy outcomes, which lead us to test whether viral infections play a role in development of preeclampsia [19,20]. Our previous studies reported that activation of TLR3, a double-stranded RNA receptor, with the double-stranded viral RNA mimetic polyinosinic:polycytidylic (poly I:C) caused inflammation, proteinuric hypertension, and endothelial dysfunction in rats and mice only if they were pregnant [21,11].…”
mentioning
confidence: 99%
“…Other maternal complications that have been associated with UTIs during pregnancy are hypertension and preeclampsia (Conde-Agudelo et al, 2008;Rustveld et al, 2008), anemia (Fede, 1983), chorioamnionitis and endometritis (Schieve et al, 1994;Delzell & Lefevre, 2000). The causal nature of these associations is questionable, because it is not always clear whether an episode of UTI preceded the particular outcome of interest, especially in what concerns maternal hypertension and anemia (Schieve et al, 1994).…”
Section: ) a L T H O U G H B A C T E R E M I A I S D E T E C T E mentioning
confidence: 99%